The humanity principle in regard to coup de grâce in armed conflicts reviewed from the perspective of international humanitarian law - Eliza Fanyeeteng; Anak Agung Sri Utari (Priviet Social Sciences Journal, 2026)
Coup de grâce is a practice that has been deeply ingrained throughout military history. Although this practice has been prohibited by various conventions, violations still occur because of differences in views between soldiers and legal scholars. The purpose of this study is to analyze and examine the practice of euthanasia or coup de grâce that occurs on the battlefield during armed conflict, based on the principle of humanity from the perspective of International Humanitarian Law. This study employs the normative legal research method with statute and conceptual approaches. The result of this study shows that coup de grâce cannot be justified in the eyes of International Humanitarian Law even with the knowledge that it is done based on mercy towards an excessively injured combatant, remembering the principle of humanity and differentiation as the basis of International Humanitarian Law. Therefore, coup de grâce  can be classified without a doubt as a war crime.